Na spotkanie z nieobecnością. "Tornerai" Justyny Bargielskiej - Brysiak, Anna M. (Colloquia Litteraria, 2024)
The purpose of this essay is to analyze and interpret the poem titled „Tornerai” from the debut volume Dating sessions (2003) published by Justyna Bargielska. The choice is due to the assumption that the said work seems to be emblematic of the Polish poet’s oeuvre. On the one hand, it perfectly fits in with the dominant motifs present in her poetry, such as loss, death, trauma, loneliness, or abandonment, on the other hand, it shows fragmentary and oneiric poetic imagery, as well as the author’s characteristic fascination with foreignness, both linguistic and thematic. In addition, as the article attempts to demonstrate, the analyzed poem brings to the fore an autobiographical theme, that of miscarriage, which, also in Bargielska’s later texts, rises even to the status of a driving mechanism of most of her works.